2011
DOI: 10.1038/jcbfm.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

Kollidon VA64, a Membrane-Resealing Agent, Reduces Histopathology and Improves Functional Outcome after Controlled Cortical Impact in Mice

Abstract: Loss of plasma membrane integrity is a feature of acute cellular injury/death in vitro and in vivo. Plasmalemma-resealing agents are protective in acute central nervous system injury models, but their ability to reseal cell membranes in vivo has not been reported. Using a mouse controlled cortical impact (CCI) model, we found that propidium iodide-positive (PI + ) cells pulse labeled at 6, 24, or 48 hours maintained a degenerative phenotype and disappeared from the injured brain by 7 days, suggesting that plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…However, plasmalemma resealing may not be sufficient for survival of injured cells. 7 In the current study, cultured primary neurons treated with post-injury P188 showed a remarkable recovery of the morphology characteristic of sham (uninjured) cells. Moreover, P188 treatment significantly attenuated cell death and LDH leakage in neurons following VCSD.…”
Section: P188 Effect On Tbi-induced Damagementioning
confidence: 89%
See 2 more Smart Citations
“…However, plasmalemma resealing may not be sufficient for survival of injured cells. 7 In the current study, cultured primary neurons treated with post-injury P188 showed a remarkable recovery of the morphology characteristic of sham (uninjured) cells. Moreover, P188 treatment significantly attenuated cell death and LDH leakage in neurons following VCSD.…”
Section: P188 Effect On Tbi-induced Damagementioning
confidence: 89%
“…1,7 Previous experiments have tested poloxamer 188 following in vivo traumatic brain injury and these studies have indicated a therapeutic effect of the treatment. 7 The VCSD configuration applied to cells cultured on a rigid substrate is not intended to mimic explicitly the in vivo, three-dimensional tissue deformation that occurs during injury. 8,20 Rather, the mechanical loading profile was developed and used to replicate the characteristics of cellular injury observed in vivo.…”
Section: P188 Effect On Tbi-induced Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Motor test was performed as previously described [15]. Mice were gently grasped by the tail and placed on a 35 cm taut wire suspended between two upright wooden bars 50 cm above a padded table.…”
Section: Methodsmentioning
confidence: 99%
“…39 Furthermore, it seems that neurons with plasmalemma damage will inevitably degenerate and die by 7 days after CCI, even though some neurons are found to undergo spontaneous resealing of the damaged plasma membrane, suggesting that permeable plasmalemma after TBI is probably fatal to neurons. 13,40 Similarly, although the ruptured somata membrane could be repaired by using a membrane-resealing agent Kollidon VA64, such effective repairing of the membrane does not rescue the injured neurons. 40 Repairing the injured CNS remains a major challenge in neurotrauma research.…”
Section: Discussionmentioning
confidence: 99%